THE EFFECT OF READING COMPREHENSION SKILLS ON ABILITY TO SOLVE MATH WORD PROBLEMS TO FOURTH GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN KEBUMEN SUB-DISTRICT IN ACADEMIC YEAR OF 2020/2021 - Afrida Muarifa; Ngatman Ngatman; Ratna Hidayah (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
The research aimed to determine the effect of reading comprehension skills on the ability to solve math word problems and to determine the contribution of reading comprehension skills on the ability to solve math word problems to fourth grade students of public elementary schools in Kebumen Sub-district in academic year of 2020/2021. The research was a quantitative research with regression method. The population were all fourth grade students in Kebumen Sub-district. The samples were 324 fourth grade. Sampling method was probability sampling technique. The data collection technique used tests. The results showed that there was a positive and significant effect between reading comprehension skills on the ability to solve math word problems to fourth grade students of public elementary schools in Kebumen Sub-district in academic year of 2020/2021. The value of determination coefficient (R Square) was 0.214. The reading comprehension skills contributed 21.3% on the ability to solve math word problems and the remaining 78.7% was influenced by other factors.   Penelitian ini bertujuan untuk mengetahui adanya pengaruh kemampuan membaca pemahaman terhadap kemampuan menyelesaikan soal cerita matematika dan mengetahui besarnya sumbangan kemampuan membaca pemahaman terhadap kemampuan menyelesaikan soal cerita matematika siswa kelas IV SD Negeri se-Kecamatan Kebumen Tahun Ajaran 2020/2021. Penelitian ini merupakan penelitian kuantitatif dengan metode regresi. Populasi penelitian ini adalah seluruh siswa kelas IV SDN se-Kecamatan Kebumen. Sampel pada penelitian ini berjumlah 324 siswa yang dipilih secara acak dengan teknik probability sampling. Teknik pengumpulan data yang digunakan dalam penelitian ini berupa tes. Hasil penelitian ini menunjukkan terdapat pengaruh positif dan signifikan antara kemampuan membaca pemahaman terhadap kemampuan menyelesaikan soal cerita matematika siswa kelas IV SDN se-Kecamatan Kebumen tahun ajaran 2020/2021 dengan nilai (R Square) sebesar 0,214. Kemampuan membaca pemahaman memberikan sumbangan terhadap kemampuan menyelesaikan soal cerita matematika sebesar 21,3 % dan sisanya sebesar 78,7 % dipengaruhi oleh faktor lain.